2022
DOI: 10.3389/fpsyg.2022.769930
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Activity and Depressive Symptoms During COVID-19 Lockdown: United States Adult Age Groups

Abstract: This study investigates: (1) the changes in three major health-related factors—physical activity, non-physical-activity health behavior (i.e., diet quality, alcohol consumption, smoking, sleep quality), and depressive symptoms, and (2) how changes in physical activity were associated with changes in one’s depressive symptoms among young adults, middle-aged adults, and older adults while controlling non-physical-activity health behavior and sociodemographic characteristics among young, middle-aged, and older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…Globally, the COVID-19 pandemic has negatively affected PA levels among older adults [8]. As compared to the time before COVID-19, studies consistently observed a decline in PA level among older adults after the COVID-19 outbreak [9][10][11][12][13][14][15][16][17][18]. Similar trends were observed in Hong Kong.…”
Section: Introductionsupporting
confidence: 52%
“…Globally, the COVID-19 pandemic has negatively affected PA levels among older adults [8]. As compared to the time before COVID-19, studies consistently observed a decline in PA level among older adults after the COVID-19 outbreak [9][10][11][12][13][14][15][16][17][18]. Similar trends were observed in Hong Kong.…”
Section: Introductionsupporting
confidence: 52%
“…Since late 2019, the COVID-19 pandemic has significantly impacted one's active lifestyle (Kim et al, 2022 ). On the one hand, social distancing/isolation restrictions prevented the public from being physically active in that sports events were suspended, postponed, or paused.…”
mentioning
confidence: 99%